1996
DOI: 10.1128/jb.178.10.2960-2970.1996
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in fliK and flhB affecting flagellar hook and filament assembly in Salmonella typhimurium

Abstract: Mutations in the fliK gene of Salmonella typhimurium commonly cause failure to terminate hook assembly and initiate filament assembly (polyhook phenotype). Polyhook mutants give rise to pseudorevertants which are still defective in hook termination but have recovered the ability to assemble filament (polyhook-filament phenotype). The polyhook mutations have been found to be either frameshift or nonsense, resulting in truncation of the C terminus of FliK. Intragenic suppressors of frameshift mutations were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
292
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(302 citation statements)
references
References 27 publications
10
292
0
Order By: Relevance
“…However, the placements of spa32, invJ, fliK, and yscP in the respective operons were all similar, and each of the gene products was secreted (6,32,36,40,42; this study). Furthermore, the production of each protein was required for a functional type III secretion system (Spa32, InvJ, and YscP) (7, 36, 42; this study) or flagellar export system (FliK) (20,33,48). Consequently, we wondered whether Spa32 and its putative cognates would share similar functions.…”
Section: Resultsmentioning
confidence: 99%
“…However, the placements of spa32, invJ, fliK, and yscP in the respective operons were all similar, and each of the gene products was secreted (6,32,36,40,42; this study). Furthermore, the production of each protein was required for a functional type III secretion system (Spa32, InvJ, and YscP) (7, 36, 42; this study) or flagellar export system (FliK) (20,33,48). Consequently, we wondered whether Spa32 and its putative cognates would share similar functions.…”
Section: Resultsmentioning
confidence: 99%
“…Orthologues of HP1575 occur in several other bacteria and are referred to as FlhX proteins (Pallen et al, 2005; Wand et al, 2006). Wand and co-workers reported that FlhX can functionally substitute for FlhB CC in H. pylori (Wand et al, 2006), suggesting that in the absence of FlhB CC , FlhX can associate with the N-terminal subdomain of FlhB C (FlhB CN ).As observed in S. typhimurium, disruption of H. pylori fliK (hp0906) results in reduced motility and formation of polyhook structures due to a delay in the switch between export states (Ryan et al, 2005;Williams et al, 1996). Inactivation of fliK in H. pylori and C. jejuni stimulates expression of RpoN-dependent flagellar genes (Kamal et al, 2007;Ryan et al, 2005).…”
mentioning
confidence: 95%
“…These results are in line with earlier findings showing that the 33 last amino acids of FlhB are redundant for hook-basal body assembly. Interestingly this domain of FlhB has an inhibitory effect on the substrate specificity switch suggesting that the C-terminal region of FlhB is involved in the temporal regulation of the flagellum assembly (33,34). In fact it cannot be excluded that YscU via its C-terminal secretion signal possesses a negative activity similarly to FlhB, that affects the switch from secretion of early to late substrates.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated the involvement of the YscU/FlhB family of protein in the substrate specificity switch (11,13,14,34). YscU is anchored in the inner membrane via four transmembrane segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation